Applying the socio-ecological model to understand community reintegration experiences among individuals on opioid agonist treatment (OAT) released from federal incarceration in Ontario, Canada - Cayley Russell; Michelle Pang; Frishta Nafeh; Shanna Farrell MacDonald; Dena Derkzen; Jürgen Rehm; Benedikt Fischer (Elsevier, 2022)
Introduction: Correctional populations on opioid agonist treatment (OAT) experience adverse outcomes upon community release. However, many factors impact post-release community reintegration experiences/trajectories, and few studies examine the complex interplay between these dynamics. The current study utilized the socio-ecological model (SEM) to examine the synergistic impact of individual, interpersonal, community, and organizational/policy-level factors on reintegration experiences among individuals on OAT released from federal incarceration in Ontario, Canada. Methods: This article describes findings from the follow-up component of a longitudinal mixed-methods study examining community transition experiences among 35 individuals engaged in correctional OAT. Interviews took place within one-year post-release. Questions focused on community transition experiences. Thematic analyses were conducted on the qualitative data. We utilized the SEM framework to illustrate the overarching themes that shaped participant's post-release experiences. Results: Participants described a number of factors that influenced community re-integration. Participants identified the interaction between individual- (e.g., health concerns and personal motivation/coping skills), interpersonal- (e.g., family dynamics and social networks), community- (e.g., employment/education, housing, and health and addiction care) and organizational/policy- (e.g., discharge planning, release obligations, and financial policies) level factors as influential to community reintegration. Conclusions: This study provides insight into the ways that different post-release dynamics work alone and together to impact an individual's ability to meet their post-incarceration release requirements and goals. Suggestions for key interventions and multi-sectoral strategies that take into account the intersecting determinants highlighted in this study to better support the re-entry process for Canadian federal correctional populations on OAT are discussed and provided.